Survivin expression and its potential clinical significance in gastrointestinal stromal sarcoma - DANE, FAYSAL (ELSEVIER SCIENCE BV, 2011)
This study was designed to determine the level of survivin expression and its clinical significance as a prognostic factor in gastrointestinal stromal sarcoma (GIST). Twenty patients (12 males and 8 females) ranging in age from 25 to 72, with a median age of 53 were evaluated. Failure of TKI treatment was higher in the survivin-positive group (p= 0.06). The rate of metastasis was significantly higher in the survivin positive group vs. the negative group (80% vs. 30%, p =0.18). The median overall survival (OS) time was 114 (range 29-199) months, and the median disease-free survival (DFS) time was 88 (range 40-135) months. The median progression-free survival (PFS) time was 40 (range 24-55) months. Further, a comparison of patients with survivin positive versus negative tumors, revealed no significant difference for OS, DFS, and PFS (p = 0.45, p = 0.19, p= 0.55, respectively), number of mitoses in 50 HPF (p =0.14), and tumor size (p = 0.94). In conclusion, survivin was highly expressed in GISTs, although we found no correlation between survivin expression and PFS, DFS and OS, survivin may be a predictive marker in GISTs for disease progression. We believe that additional studies are warranted to determine the clinical significance of survivin expression as a prognostic or predictive marker in patients with GIST. Crown Copyright (C) 2011 Published by Elsevier B.V. All rights reserved.
Keywords: Survivin; Anti-apoptosis; Inhibitors of apoptosis proteins; Gastrointestinal stromal sarcoma; ANTI-APOPTOSIS GENE; DIFFERENTIAL-DIAGNOSIS; THERAPEUTIC TARGET; CELL-PROLIFERATION; PROGNOSTIC-FACTORS; PANCREATIC-CANCER; GASTRIC-CANCER; GROWTH-FACTOR; TUMORS; INHIBITOR